RECUPERAR LA CIUDAD: APROXIMACIONES A LAS EXPERIENCIAS DE HABITAR LO PÚBLICO Y LO PRIVADO EN LEÓN, GUANAJUATO - Claudia Teresa Gasca Moreno; Aquiles Omar Ávila Quijas; Luis Ángel Chía Calvillo (Xihmai, 2026)
The study of urban expansion in Mexican cities, including León, Guanajuato, is key to understanding inequalities in access to urban space. New components of the expanding urban morphology, such as gated housing developments for different socioeconomic groups, plazas, and shopping centers, have produced environments ranging from highly exclusive to those serving less advantaged sectors. In recent years, these urban forms have increasingly prioritized enclosure and privatization, revealing a reconfiguration of the public realm as an expression of growing social fragmentation. This proposal seeks to explore this reconfiguration and reflect, through the case of León, on how urban planning and development have triggered fragmentation processes. It offers an initial approach to the dynamics between public and private spaces and their effects on ways of living and inhabiting the city.